ANALISIS PEMBELAJARAN KLINIK KEPERAWATAN UNTUK MENCAPAI STANDAR KOMPETENSI UNGGULAN ASUHAN KEPERAWATAN GAWAT DARURAT PADA MAHASISWA AKPER INSAN HUSADA SURAKARTA - Saka Suminar (STIKES Wira Husada Yogyakarta, 2018)
Background: Science-oriented education and technology means that nursing education always follows the development of science and technology in health and nursing. The educational curriculum is developed based on educational goals that are directed at meeting the needs of the community and the development of health in the future by taking into account the demands of the nursing profession. In this book a core curriculum is developed containing 70% of the curriculum of the Nursing Diploma III Program and should be added 30% curriculum developed by the institution according to the needs and vision of the institution concerned. Based on the framework of reference, then Akper Insan Husada develops as well as leading the study program and listed in the vision of the study program: Become a Diploma III Nursing Program competent, competitive, character and excellence in the ﬁ eld of emergency at the National level in 2024. The purpose of research is To describe the learning process of nursing clinics in Akper Insan Husada Surakarta to achieve the Competence Standards of emergency nursing care nursing.Subjects and Methods: The subjects of the study were all students who were undergoing emergency clinic at the hospital. The research type or method chosen is descriptive qualitative analysis. Qualitative research to further explore the data and information (exploration) so that can be known opinion and views of managers, pengampu and students to the learning process of emergency nursing clinics. Result: 1. Planning has been arranged properly and systematically according to emergency competency in curriculum 2014. Still there is difference of perception of RPP model that will be used, so that will confuse the pengampu and student who become clinic implementer. 2. The emergency clinic practice period is carried out in accordance with the place and time, ie in emergency and inroom emergency rooms with competent structural guidance that has been appointed by the hospital based on capability and ﬁllings and expertise in the ﬁeld. 3. Evaluation of learning Emergency Nursing Clinic Most of the lecturers and clinical supervisors have been carrying out the process of guidance and evalausi on students with good period of time speciﬁed.Conclusion: The result of the study implies that Insan Husada Surakarat as a nursing education institution needs to improve the quality of learning and the quality of the lecturer or the instructor of the ﬁeld clinic.